Spraying Agricultural Crops Based on Internet of Things (IoT) - Shofiatul Ula, M.Eng.; Sidik Susilo; Erny Listijorini; Raka Irawan; Aceng Sambas; Aldis Tia Assidiq (Universitas Sultan Ageng Tirtayasa, 2021)
Indonesia's Agriculture is a strategic sector in increasing economic growth. One of the efforts to increase agricultural production in Indonesia is through technology. Smart farming models can be developed to improve the efficiency and effectiveness of farmland management. The monitoring and watering regulation system using IOT has many benefits, including time efficiency, work effectiveness, remote operation, simplicity, and better irrigation accuracy. In this study, the Smart Farming Device was placed in a coastal area with a hot climate in the chili garden. The experiment was conducted 9 hours from 08.00 – 17.00 WIB (West Indonesian Time). The Smart Farming Device works in a modular manner controlled remotely by the internet network, which works by energy converted from the sunlight. The use of types of sensors and the sensors placed on the farmland will determine the accuracy of the information received by farmers. From the sensors parameter, we found that spraying water to the farmland does not raise the soil moisture. A wind speed sensor needs to be added to the device to determine the effect of wind blow on the environmental parameters of the farmland. The irrigation method looks more promising for improving soil moisture conditions than the method of spraying water through the air.